Digital gap after the pandemic. Digital inclusion indicators in the educational sector (Revista Innova Educación, 2023)
The post-pandemic represents, in many aspects, a period in which a closer relationship with the use of electronic devices is evident; However, the digital divide continues to exist for some sectors of society; The objective was to make known, through specific indicators, the magnitude of the digital divide in an educational community in the "new normal"; The methodology was mixed, through the implementation of structured surveys (quantitative) and their analysis in conjunction with the group of teachers (qualitative); The results indicate an increase in devices and connectivity lines, lack of continuity in the use of digital applications in the transition to face-to-face modality and new behaviors against the use of devices, such as the increase in the consumption of content from social networks and in some cases, a routine that implies too much time in front of screens, With which it can be determined that many of the digital inequalities are related more to the inappropriate use of devices, than to the difficulty of accessing or the availability of time.
Keywords: digital inclusion indicators; digital gap; ICT; post-pandemic